Population dynamics and stock assessment of Colossoma macropomum caught in the Manacapuru Lake system (Amazon Basin, Brazil) - Campos, C. P.; Sousa, R. G. Costa; Catarino, M. F.; Costa, G. de Albuquerque [UNESP]; Freitas, C. E. C. (Wiley-Blackwell, 2015)
Colossoma macropomum is the second largest scaled fish in the Amazon basin. Reduced harvests in recent decades suggest that populations of this species are already overexploited in some areas. In this study, the population dynamics of C. macropomum was investigated using length and weight data for fish caught in the Manacapuru Lake system, a large ria lake located along the lower reach of the Solimoes River. A total of 1270 individuals of C. macropomum with standard lengths varying from 17 to 62 cm and mean length of 31.0 +/- 6.7 cm were sampled. Weights varied from 165 to 8195 g, and mean weight was 1148.3 +/- 883.8 g. Maximum sustainable yield was estimated at 285.8 g recruit(-1), corresponding to a fishing mortality of 0.51 year(-1). A scenario analysis based on changes in fishing mortality and age at first capture, two parameters potentially addressed by fishing management strategies, suggested that any improvement in fishing yield depends on increases in age at first capture.
Keywords: amazon basin; growth; maximum sustainable yield; mortality; overfishing; tambaqui